The Role of Error Type and Working Memory in Written Corrective Feedback Effectiveness on First-Language Self Error-Correction. (April 2021) - Nowbakht, Mohammad; Olive, Thierry
This study examined the role of error-type and working memory (WM) in the effectiveness of direct-metalinguistic and indirect written corrective feedback (WCF) on self error-correction in first-language writing. Fifty-one French first-year psychology students volunteered to participate in the experiment. They carried out a first-language error-correction task after receiving WCF on typographical, orthographic, grammatical, and semantic errors. Results indicated that error-type affected the efficacy of WCF. In both groups, typographical error-correction was performed better than the others; orthographic and grammatical error-correction were not different, but both were corrected more frequently than semantic errors. Between-group comparisons showed no difference between the two groups in correcting typographical, orthographic, and grammatical errors, while semantic error-correction was performed significantly better for the direct group. Results revealed that WM was not involved in correcting typographical, orthographic, and grammatical errors in both groups. It did, however, predict semantic error-correction only in response to direct-metalinguistic WCF. In addition, the processing component of WM was predictive of semantic error-correction in the direct WCF group. These findings suggest that error-type mediates the effectiveness of WCF on written error-correction at the monitoring stage of writing, while WM does not associate with all WCF types efficacy at this stage.